Asnaf Fisabilillah in Meeting The Needs of The Ummah: Its Limitations and Flexibilities - Achmad, Noor (Center of Strategic Studies (PUSKAS) BAZNAS, 2024)
Asnaf fisabilillah has a very broad, universal scope and tends to be multi-interpretive. This general nature results in differences of opinion among scholars in interpreting it. Limiting the meaning of fisabilillah to only jihad or fighting to take up arms against the enemies of Islamis considered irrelevant in today's contemporary context. Therefore, this paper will discuss in detail the distribution of zakat funds for asnaf fisabilillah in its role to meet the needs of the people in the contemporary era by examining its implementation in Indonesia. This paper isexpected to be a guide and inspiration for zakat managers, policy makers, and the general public in maximizing the potential of zakat funds, especially in the asnaf fi sabilillah category.